Epigenetic silencing of microRNA-203 is required for EMT and cancer stem cell properties - Taube, Joseph H. (Nature Publishing Group, 2013)
The epithelial-mesenchymal transition (EMT) imparts metastatic competence on otherwise non-metastatic cancer cells through decreased inter-cellular adhesions, increased migratory capacity, stem cell properties and anoikis and chemotherapy resistance. In this study, we profiled changes in microRNA expression during EMT in conjunction with changes in DNA methylation at microRNA promoters to discover essential mediators of EMT-imparted stemness properties. MicroRNA-203 (miR-203) expression is repressed following EMT induced by multiple different stimuli and in established claudin-low cell lines as well as the CD44hi/CD24lo stem cell-enriched fraction. Expression of miR-203 in mesenchymal cells compromises migratory and invasive capacity in vitro, and tumor initiation and metastasis in vivo. Unexpectedly, miR-203 expression affects the sphere-forming capacity of neighboring cells by indirectly enhancing expression of DKK1, a secreted inhibitor of Wnt signaling and stemness resulting in suppression of β-catenin protein levels. Our data suggest that restoring miR-203 expression levels may inhibit metastasis and combat deregulated Wnt signaling.